Batch and fixed bed sorption of low to moderate concentrations of aqueous per- and poly-fluoroalkyl substances (PFAS) on Douglas fir biochar and its Fe3O4 hybrids. (December 2022) - Rodrigo, Prashan M.; Navarathna, Chanaka; Pham, Michael T.H.; McClain, Sarah J.; Stokes, Sean; Zhang, Xuefeng; Perez, Felio; Gunatilake, Sameera R.; Karunanayake, Akila G.; Anderson, Renel; Thirumalai, Rooban V.K.G.; Mohan, Dinesh; et al.
Abstract: Per- and poly-fluoroalkyl substances (PFAS) can cause deleterious effects at low concentrations (70 ng/L). Their remediation is challenging. Aqueous μg/L levels of PFOS, PFOS, PFOSA, PFBS, GenX, PFHxS, PFPeA, PFHxA, and PFHpA (abbreviations defined in Table 1) multi-component adsorption (pH dependence, kinetics, isotherms, fixed-bed adsorption, regeneration, complex matrix) was studied on commercial Douglas fir biochar (BC) and its Fe3 O4 -containing BC. BC is a waste product when syn-gas is produced in a large scale from wet Douglas fir wood fed to gasification at 900–1000 °C and held for 1–20 s. This generates a relatively high surface area (∼700 m 2 /g) and large pore volume (∼0.25 cm 3 /g) biochar. Treatment of BC with FeCl3 /FeSO4 and NaOH to chemically precipitate Fe3 O4 onto BC. BC and its magnetic Fe3 O4 /BC analogue rapidly adsorbed (20–45 min equilibrium time) significant amounts of PFOS (∼14.6 mg/g) and PFOA (∼652 mg/g) at natural waters' pH range (6–8). Adsorption from μg/L concentrations has produced remediated aqueous PFAS concentrations of ∼50 ng/L or below the detection limits, which is closing in on EPA advisory limits. Column capacities of PFOS were 215.3 mg/g on BC and 51.9 mg/g Fe3 O4 /BC vs 53.0 mg/g and 21.8 mg/g, respectively, for PFOA. Hydrophobic and electrostatic interactions are thought to drive this sorption. Successful stripping regeneration by methanol was achieved. Thus, hydrophobic Douglas fir biochar produced by fast high temperature pyrolysis and its Fe3 O4 /BC analogue are adsorbent candidates for PFAS remediation from the dilute PFAS concentrations often found in polluted environments. Small Fe3 O4 /BC particles can be magnetically removed from batch treatments avoiding filtration. Graphical abstract: Image 1 Highlights: Trace PFOS and PFOA were remediated using commercial Douglas fir biochar variants. PFOS column capacities were 48–210 mg/g and PFOA capacities were 17–48 mg/g. Post sorption mixtures gave PFAS levels of ∼50 ppt or below the detection limits. Micelle driven hydrophobic sorption interactions were sought to be predominant.